1995
DOI: 10.2224/sbp.1995.23.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation and Depression in Eating Disorders

Abstract: Measures of dissociation and depression were obtained from 26 women with anorexia nervosa, 18 with bulimia nervosa, and 31 non eating disordered controls using the Questionnaire of Experiences of Dissociation (Riley, 1988) and the Beck Depression Inventory (Beck, Ward, Mendelson, Mock, & Erbaugh, 1961). Eating disordered subjects scored significantly higher on both dissociation and depression than non eating disordered subjects. A moderate positive correlation was found between dissociation and depression in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Bias may result from over or underreporting due to such factors as mood congruence, suggestibility, expectations, and participants' causal beliefs relating to symptoms. In particular, the increased depression which has been found among bulimics (Brotman, Herzog, & Woods, 1984;Greenes et al 1993;Hinz & Williamson, 1987;Schumaker et al, 1995;Williamson et al, 1987) might have meant that more negative memories were recalled and reported (mood congruence effect; Brewin, Andrews, & Gotlieb, 1993). It is possible that the greater severity (but not more frequent overall occurrence) of CSA reported by CBs might indeed be due to this mood congruence effect.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Bias may result from over or underreporting due to such factors as mood congruence, suggestibility, expectations, and participants' causal beliefs relating to symptoms. In particular, the increased depression which has been found among bulimics (Brotman, Herzog, & Woods, 1984;Greenes et al 1993;Hinz & Williamson, 1987;Schumaker et al, 1995;Williamson et al, 1987) might have meant that more negative memories were recalled and reported (mood congruence effect; Brewin, Andrews, & Gotlieb, 1993). It is possible that the greater severity (but not more frequent overall occurrence) of CSA reported by CBs might indeed be due to this mood congruence effect.…”
Section: Discussionmentioning
confidence: 97%
“…For other bulimics, there may be other etiological factors involved in the maintenance of both dissociative and bulimic behaviors. In particular, bulimic behaviors themselves are profound physiological stressors which often coexist with psychological symptoms such as depression (Schumaker et al, 1995;Zerbe et al 1993) and anxiety (Kerr, Skok, & McLaughlin, 1991). Demitrack et al (1990) have proposed that these behaviors may "alter the individual's conscious state or alternatively serve as contextual cues for the induction of dissociative states and in so doing perpetuate or enhance the propensity of the patient to dissociate" (p. 1187).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, panic disorder patients who experience such episodes also report more severe dysfunction as evidenced by increased depression, stress, trait anxiety, and fear of panic symptoms (Miller, Brown, DiNardo, & Barlow, 1994). In addition to dissociative disorders, periods of unreality have been reported among individuals with posttraumatic stress disorder and eating disorders (e.g., Schumaker, Warren, Carr, Schreiber, & Jackson, 1995;Van der Kolk, Pelcovitz, Roth, & Mandel, 1996). Thus, identification of exercises that induce these episodes may be useful in the treatment of a range of psychological problems.…”
mentioning
confidence: 99%